MicroRNA Regulation of DNA Repair Gene Expression in Hypoxic Stress - Crosby, Meredith E.; Kulshreshtha, Ritu; Ivan, Mircea; Glazer, Peter M. (Cancer research (Chicago, Ill.), 2009)
Genetic instability is a hallmark of cancer; the hypoxic tumor microenvironment has been implicated as a cause of this phenomenon. MicroRNAs (miR) are small nonprotein coding RNAs that can regulate various cellular pathways. We report here that two miRs, miR-210 and miR-373, are up-regulated in a hypoxia-inducible factor-1α–dependent manner in hypoxic cells. Bioinformatics analyses suggested that these miRs could regulate factors implicated in DNA repair pathways. Forced expression of miR-210 was found to suppress the levels of RAD52, which is a key factor in homology-dependent repair (HDR); the forced expression of miR-373 led to a reduction in the nucleotide excision repair (NER) protein, RAD23B, as well as in RAD52. Consistent with these results, both RAD52 and RAD23B were found to be down-regulated in hypoxia, but in both cases, the hypoxia-induced down-regulation could be partially reversed by antisense inhibition of miR-210 and miR-373. Importantly, luciferase reporter assays indicated that miR-210 is capable of interacting with the 3′ untranslated region (UTR) of RAD52 and that miR-373 can act on the 3′ UTR of RAD23B. These results indicate that hypoxia-inducible miR-210 and miR-373 play roles in modulating the expression levels of key proteins involved in the HDR and NER pathways, providing new mechanistic insight into the effect of hypoxia on DNA repair and genetic instability in cancer. [Cancer Res 2009;69(3):1221–9]